O céu que nos protege: a desertificação das relações humanas - Rodrigues, Ana Claudia (2014)
And the world at full speed, with its re-engineering and mass production, would bring hope to men. It was possible to believe in the prosperity of technique as a compensation for the gap imposed by the Second World War. In a blend of sepia and black and white, reminder of a bygone cinema, the screen is filled as progress, speed and the principle of quantitative values are announced. Industries and factories, cars and trams, dynamism and rush, skyscrapers and neon: here is the synthesis of the universe portraited in the beginning of The sheltering sky (1990), by Bernardo Bertolucci. As colours invade the screen, through a sequence of shots, as they indicate new happenings, the essence of all that excess was made as though it was pulled away with tweezers: Port, Kit and Tunner would lead, starting from that diegetic instant, not only their own peculiarities, but also the universalization they fitted in. Thus, in the face on the mentioned anticipating elements of a leading image for the awake senses of the spectators, we seek to analyze Bertolucci s film in the meanderings of its own historical contextualization in which the characters are inserted, since they would be sharp representation of a recent second post-war, and they saw their own rebuilding in the progress of technique and therefore, through this idealization, they walked forward searching for the compensation of intrinsic gaps. But it is clear that the characters behaviour will not be restricted to the 50s but rather on the contrary, once in earlier circunstances the individuals can be seen in the look for a path, a way out from their loneliness or any other aspect concerning the sense of their existence. In the same way, nowadays , by the means of a visible technology serving a market in constant renovation, anchors reshaped in new disguises are evident, remoulding the idea of new , are evident, and these are constantly committed to the compensation of an existencial void, of a crossing in the quest for a hold for the individual. So, starting from the very genesis of the film precursor tracks common to the creative progress, of which there are no certainties, but intuition, deduction sensitive to the heterogeneous remittance of art, the route narrated in each segment of the film will be establishing itself gradually, always by the light of a methodology fit to outline each character by their own action in order to insert them in the categories given by the diegesis itself, such as travellers, tourist and those who would be in the simultaneity of those determinations, which we can name passengers all of this indicating different manners of seeing the world. Alongside whit those classifications, it is sought to establish the very path of the aesthetic element through the trails of those individuals, first in a fleeting principle, that is, easily falling in forgetfulness, through the linkage of a time in synchrony with the past of tradition, with the present of its fulfillments and with the future pointing at wherever there may be a look of reception. Thus, between the ephemerity of things and the firmness of senses, between men s trends in the front of their supposed arts and of the perennial building of the individual mirroring himself in the immortality of the artistic object, this analysis of the film The sheltering sky begins.